TRADISI SIRIT MASYARAKAT LAMPUNG DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - nency dela oktora (Institut Agama Islam Negeri Metro, 2017)
Marriage is one of the laws that apply to all the creatures of Allah are dead. Sirit is carry off a woman by force, deceit sense, even violence to marry. Problematic is that Sirit is not in accordance with the concept of marriage in Islam is that her marriage was valid if it meets the requirements of marriage is one of the conditions is the willingness between two potential partner, which may mean that that marriage should not be forced to either party. The formulation of the problem are (1) the factors behind the occurrence of Sirit?, (2) How is the operational / implementation and impact Sirit ?, and (3) How Sirit Lampung ethnic communities in the Perspective of Islamic Family Law. Objective: (1) Knowing the factors that cause Sirit in Lampung ethnic society, (2) Explain the operational/ implementation Sirit and the impact Sirit, (3) Analyze Sirit Lampung ethnic society in the perspective of the Islamic Family Law. Data collection methods used was interviews and documentation. Data analysis method used is qualitative method. Based on the analysisof, it was concluded that the factors that caused the most dominant Sirit is a lack of awareness of self or less of its sturdywalls of faith to comply with religious law and customary law, economic factors, and self-controlfactor(liver). Sirit is done by means of deceit, coercion and even violence and some aresexually abused. Sirit can not be justified because Islam does not teachsuch things, as explained in Firman of Allah and the Hadis is the Hadis is more concerned with the right of a woman to decide a case which is about the marriage of their own. If viewed from the eyes of urf' the tradition Sirit is customary imperfect, that is not in accordance with the texts of Personality 'so that this tradition must be rejected or abandoned. Perkawinan merupakan salah satu sunnatullah yang berlaku untuk semua makhluk Allah SWT yang bernyawa. Sirit adalah membawa lari perempuan dengan cara paksa, akal tipu daya, bahkan kekerasan untuk dinikahi. Problematika nya, bahwa sirit tidak sesuai dengan konsep perkawinan dalam Islam menyebutkan sahnya pernikahan jika memenuhi syarat-syarat perkawinan yaitu adanya kerelaan antara dua calon pasangan. Permasalahan yang dibahas yaitu tradisi sirit masyarakat suku Lampung Perspektif Hukum Keluarga Islam. Tujuan (1) Mengetahui faktor-faktor yang menyebabkan terjadinya sirit masyarakat suku Lampung, (2) Menjelaskan operasional/pelaksanaan sirit dan dampak sirit, (3)Menganalisis sirit masyarakat suku Lampung dalam perspektif Hukum Keluarga Islam. Metode pengumpulan data berupa wawancara dan dokumentasi. Metode analisis data menggunakan metode kualitatif. Berdasarkan hasil analisis disimpulkan Faktor-faktor yang menyebabkan terjadinya sirit yaitu kurangnya kesadaran diri atau kurang kokoh nya tembok keimanan untuk mentaati hukum agama dan hukum adat, faktor ekonomi, dan faktor pengendalian diri (hati). Sirit dilakukan dengan cara tipu daya, paksaan bahkan dengan kekerasan serta ada juga yang mengalami pelecehan seksual. Sirit tidak dibenarkan dalam Islam, sebagaimana diterangkan dalam Firman Allah SWT dan hadis yaitu dalam hadis lebih mementingkan hak seorang perempuan dalam memutuskan sesuatu yaitu mengenai pernikahan mereka sendiri. Jika dilihat dari urf’, tradisi sirit merupakan adat yang fasid, tidak sesuai dengan nash-nash syara’ sehingga tradisi ini wajib ditolak atau ditinggalkan.